2021
DOI: 10.2807/1560-7917.es.2021.26.12.2100276
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 lineage P.1 in patients from a region with exponentially increasing hospitalisation rate, February 2021, Rio Grande do Sul, Southern Brazil

Abstract: The emergence of SARS-CoV-2 P.1 lineage coincided with a surge in hospitalisations in the North region of Brazil. In the South region’s Rio Grande do Sul state, severe COVID-19 case numbers rose 3.8 fold in February 2021. During that month, at a COVID-19 referral hospital in this state, whole-genome sequencing of a subset of cases’ specimens (n = 27) revealed P.1 lineage SARS-CoV-2 in most (n = 24). Findings raise concerns regarding a possible association between lineage P.1 and rapid case and hospitalisation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 4 publications
5
69
3
2
Order By: Relevance
“…Genomic surveillance and early data sharing by teams worldwide have led to the rapid detection and characterization of SARS-CoV-2 and new variants of concern (VOCs) ( 25 ), yet such surveillance is still limited in many settings. The P.1 lineage is spreading rapidly across Brazil ( 55 ), and this lineage has now been detected in >36 countries ( 56 ). But existing virus genome sampling strategies are often inadequate for determining the true extent of VOCs in Brazil, and more detailed data are needed to address the impact of different epidemiological and evolutionary processes in their emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic surveillance and early data sharing by teams worldwide have led to the rapid detection and characterization of SARS-CoV-2 and new variants of concern (VOCs) ( 25 ), yet such surveillance is still limited in many settings. The P.1 lineage is spreading rapidly across Brazil ( 55 ), and this lineage has now been detected in >36 countries ( 56 ). But existing virus genome sampling strategies are often inadequate for determining the true extent of VOCs in Brazil, and more detailed data are needed to address the impact of different epidemiological and evolutionary processes in their emergence.…”
Section: Discussionmentioning
confidence: 99%
“…This variant probably emerged between late November and early December 2020 in Amazonas, northern Brazil, with rapid dissemination to other regions and other countries [1]. The introduction of this variant was temporally associated with increased transmissibility of covid-19 causing a critical epidemiological scenario in different places where it was detected as the Amazonas, in the north region, and the Paraná and the Rio Grande do Sul (RS) states, in the south of the country [2][3][4][5]. In the Amazonas state, a collapse of the health system was observed, which made it difficult to assess the real impact of the P.1 variant on the lethality by covid-19, which may have increased due to the overload of the health system and not exclusively by the intrinsic characteristics of the variant [2].…”
Section: Introductionmentioning
confidence: 99%
“…Virological surveillance data showed that in February, the variant P.1 corresponded to about 70% of the viruses sequenced in the RS state. [5,7] The exponential increase in the hospitalization rate observed in the RS state could be explained, on one hand, by the P.1 circulation as this variant has being 2.6 times more transmissible (95% Confidence Interval (CI): 2.4-2.8) than the previous one [8]. However, on other hand, studies have suggested that the P.1 variant can also lead to more severe conditions, which would increase the need for hospitalization and contribute to the increase observed in hospitalization rates.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the greatest concern when it comes to emerging SARS-CoV-2 variants stems from identification of rapidly expanding lineages with mutations in the RBD that have significant impact on neutralization potency of many RBD-targeting antibodies, including clinical stage antibody therapeutics, as well as natural infection and vaccine-induced antibody responses. In addition to the N501Y mutation, the B.1.351 and P.1 lineages, originating in South Africa and Brazil respectively, also carry mutations E484K and K417N/T (Tegally et al, 2020 Preprint;Martins et al, 2021). Other lineages containing the E484K mutation but not N501Y, such as P.2 (Brazil) and B.1526 (New York), have also been expanding, suggesting that the E484K mutation independent of N501Y may confer sufficient advantages to the virus (Voloch et al, 2020 Preprint;West et al, 2021 Preprint).…”
mentioning
confidence: 99%